Beyond conceptual dualism : ontology of consciousness, mental causation and holism in John R. Searle's Philosophy of mind - Vicari, Giuseppe. (Value Inquiry Book Series, 2008)
This book is a systematic analysis of John R. Searle's philosophy of mind. Searle's view of mind, as a set of subjective and biologically embodied processes, can account for our being part of nature qua mindful beings. This model finds support in neuroscience and offers reliable solutions to the problems of consciousness, mental causation, and the self.